Generation of Human Induced Pluripotent Stem (iPS) Cells from Liver Progenitor Cells by Two Chemicals and the Clinical Application - Moriguchi, Hisashi; Mihara, Makoto; Sato, Chfumi; Chung, Raymond T (IntechOpen, 2011)
None